Pengaruh Media Pasir Kinetik Terhadap Kemampuan Pramenulis Anak - Yuniarti , Yuniarti; Rosma, Rosma; Sutrisno, Sutrisno (JEA (Jurnal Edukasi AUD), 2024)
This article is motivated by the pre-writing abilities of children who are still incapable. The resulting lines are less firm and thick, and the child's scribbles do not resemble the expected letters. Kinetic sand is one material that can be used to stimulate prewriting. This research aims to improve fine motor skills using kinetic sand as a medium. This research uses a quantitative experimental research methodology. Data collection techniques and tools used are observation, checklist, and documentation. The subjects in this research were class A children aged 4-5 years. The data analysis used was the Paired Sample T-test. The results from Pretest averaged 4.5%, while the Posttest results after being given treatment 1-3 with an average of 9%. It is known that on the Pretest and Posttest data, a t-test was carried out using the SPSS 25 with a t value of 9.00, while the t-table (df=5, significance level 5%) was 2.015. Thus the calculated t value > t table (9,000 > 2,015). It is known that the sig(2-tailed) value is 0.00<0.05, so we can conclude that there is a real difference between kinetic sand media and children's prewriting ability.